2005
DOI: 10.1111/j.1365-2435.2005.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Does water transport scale universally with tree size?

Abstract: Summary 1.We employed standardized measurement techniques and protocols to describe the size dependence of whole-tree water use and cross-sectional area of conducting xylem (sapwood) among several species of angiosperms and conifers. 2. The results were not inconsistent with previously proposed 3/4-power scaling of water transport with estimated above-ground biomass. However, for a given size, angiosperms transported considerably greater quantities of water than conifers. 3. In the angiosperms studied, the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
135
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 38 publications
(74 reference statements)
14
135
3
1
Order By: Relevance
“…Our data showed the exponents varied from 1.32 for the Dahurian larch to 2.19 for the cork-tree (Tab. V), supporting the notion proposed by Meinzer et al (2005) but with a wider exponent range. This conclusion seems plausible because there are divergences in morphological and physiological properties of water conducting system for diverse species (Hacke et al, 2006).…”
Section: Sapwood Allometrysupporting
confidence: 72%
See 2 more Smart Citations
“…Our data showed the exponents varied from 1.32 for the Dahurian larch to 2.19 for the cork-tree (Tab. V), supporting the notion proposed by Meinzer et al (2005) but with a wider exponent range. This conclusion seems plausible because there are divergences in morphological and physiological properties of water conducting system for diverse species (Hacke et al, 2006).…”
Section: Sapwood Allometrysupporting
confidence: 72%
“…2.33). However, Meinzer et al (2005) found that the exponents could be divided into at least three distinct species groupings, varying from 1.42 to 1.90 for the 25 temperate and tropical species investigated. Our data showed the exponents varied from 1.32 for the Dahurian larch to 2.19 for the cork-tree (Tab.…”
Section: Sapwood Allometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Prediction: The total energy and resource flux of all stems within a size class is independent of plant size when binned linearly with respect to stem radius. As shown previously, both theoretically (16) and empirically (15,28), the xylem flux of a tree, Q k , scales as Q k ϰ r k 2 ϰ m k 3/4 . When combined with the inverse square law for the number of trees in a bin, ⌬n k ϰ r k Ϫ2 ϰ m k Ϫ3/4 , this predicts that the total resource flux per unit area per size class, is invariant with respect to tree size.…”
Section: Empirical Results and Theoretical Extensionsmentioning
confidence: 99%
“…Various other authors have also reported a positive tree size-water consumption relationship for tropical species referring either to tree height or DBH (e.g. Andrade et al 1998, with tree height; Meinzer et al 2005, The relationship between E and vapour pressure deficit (D mean , kPa) followed an exponential form for all tree height classes. The relationship between E and solar radiation (R, MJ m −2 day −1 ) was better fitted to a first-order polynomial in all tree height classes.…”
Section: Sapwood Areamentioning
confidence: 99%